Diversity of Expression Types of Ht Genes Conferring Resistance in Maize to Exserohilum turcicum - Navarro, Barbara Ludwig; Hanekamp, Hendrik; Koopmann, Birger; von Tiedemann, Andreas (Frontiers in Plant Science, 2020)
Northern Corn Leaf Blight (NCLB) is an important leaf disease in maize worldwide and it is spreading into new areas with expanding maize cultivation, like Germany. Exserohilum turcicum, causal agent of NCLB, infects and colonizes leaf tissue and induces elongated necrotic lesions. Disease control is based on fungicide application and resistant cultivars displaying monogenic resistance. Symptom expression and resistance mechanisms differ in plants carrying different resistance genes. Therefore, histological studies and DNA quantification were performed to compare the pathogenesis of E. turcicum races in maize lines exhibiting compatible or incompatible interactions. Maize plants from the differential line B37 with and without resistance genes Ht1, Ht2, Ht3 and Htn1 were inoculated with either incompatible or compatible races (race 0, race 1 and race 23N) of E. turcicum. Leaf segments from healthy and inoculated plants were collected at five different stages of infection and disease development from penetration (0-1 dpi), until full symptom expression (14-18 dpi). Symptoms of resistance responses conveyed by the different Ht genes considerably differed between Ht1 (necrotic lesions with chlorosis), Ht2 (chlorosis and small lesions), Ht3 (chlorotic spots) and Htn1 (no lesions or wilt-type lesions). In incompatible interactions, fungal DNA was only detected in very low amounts. At 10 dpi, DNA content was elevated in all compatible interactions. Histological studies with Chlorazol Black E staining indicated that E. turcicum formed appressoria and penetrated the leaf surface directly in both types of interaction. In contrast to incompatible interactions, however, the pathogen was able to penetrate into xylem vessels at 6 dpi in compatible interactions and strongly colonized the mesophyll at 12 dpi, which is considered the crucial process differentiating susceptible from resistant interactions. Following the distinct symptom expressions, resistance mechanisms conferred by Ht1, Ht2, Ht3 and Htn1 genes apparently are different. Lower disease levels and a delayed progress of infection in compatible interactions with resistant lines imply that maize R genes to E. turcicum are associated with or confer additional quantitative resistance.